Clinical outcome after medial patellofemoral ligament reconstruction and autologous chondrocyte implantation following recurrent patella dislocation - Siebold, Rainer; Karidakis, Georgios; Fernandez, Francis (Knee surgery, sports traumatology, arthroscopy, 2014)
Medial patellofemoral ligament (MPFL) reconstruction is a well-established treatment option in recurrent patella dislocation. The combination with associated retropatellar cartilage lesions are severe injuries and very difficult to treat. The purpose of this study was to evaluate our clinical results of MPFL reconstruction and autologous chondrocyte implantation (ACI).
Gesehen am 22.07.2020